Exploring smartwatch aesthetic preferences through the Unified Model of Aesthetics - Ma, Jun; Yahaya, Mohd Faiz; Tai, Lichen; Whitfield, Allan; Barron, Deirdre (SAGE Publications Inc., 2025)
Human attempts to understand the factors involved in aesthetic preferences have a long history, extending from pure art to product aesthetics. Adopting the Unified Model of Aesthetics (UMA), this study simultaneously investigates the effects of opposing factors on stimulus aesthetic preferences from three levels: perceptual, cognitive, and social. The study used smartwatches as stimuli and was conducted on a 7-point Likert scale with 203 participants from China. The results are precise: the higher the contributions of unity at the perceptual level, typicality at the cognitive level, and connectedness at the social level, the higher the aesthetic preference. On the other hand, when the UMA model simultaneously measures the influence intensity of opposing factors, the cognitive level has the most significant influence, followed by the perceptual level, and the social level has the lowest impact. This research will provide product designers with theoretical guidance and design directions for future wearable devices.